Digitalization of Local Legislation: Potential Uses-Cases from Hungary - Szőke, Gergely László; Fábián, Adrián; Fekete, Kristóf Benedek; Horváth, Dominik; Kollár, Gergő; Lutring, Erika; Tilk, Péter (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2026)
The digitalization of local legislation can take several directions: on the one hand, the automatization of the legislative process itself (or certain elements thereof) and, on the other hand, the “coding” of the legislation that has been drafted (“Law as a Code” concept) so that it can be almost instantly implemented in the various legislative systems, thereby enabling certain legislative sub-systems to implement the “coded” legislation automatically and immediately, or enabling them to track changes automatically. In our paper, after a review of the relevant literature, we examined the possibilities and limitations of the realization of the concept in practice starting at the very first phase: what attitudes and demands can be identified by the local authorities.